2020
DOI: 10.1021/acsami.9b17680
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching in Nonperovskite-Phase CsPbI3 Film-Based Memory Devices

Abstract: Because of their attractive photoelectrical properties, perovskite-phase, CsPbX3 (X = I, Br, or Cl) materials have recently gained attention for their applications in resistive switching (RS) memories. However, phase transition of the CsPbI3 from perovskite (cubic phase) to nonperovskite (orthorhombic phase) at room temperature is problematic; it remains a challenge to apply nonperovskite CsPbI3 in RS memories. In the present work, a polymethylmethacrylate (PMMA)-assisted deposition method for nonperovskite Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 57 publications
(121 reference statements)
0
18
0
Order By: Relevance
“…To meet the growing appetite for next-generation smart storage systems and to handle the large amounts of data derived from information and communication technologies worldwide, memory, which is an integral component of electronic devices, is expected to undergo several modifications. 1 These modifications will mainly be aimed at achieving easy fabrication processes, device miniaturization, flexibility, high cycling and retention stability, low programming energy and fast switching speed. Furthermore, systems with the added advantage of flexibility provide the opportunity to be integrated in next-generation devices, such as wireless sensors, roll-up displays and wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the growing appetite for next-generation smart storage systems and to handle the large amounts of data derived from information and communication technologies worldwide, memory, which is an integral component of electronic devices, is expected to undergo several modifications. 1 These modifications will mainly be aimed at achieving easy fabrication processes, device miniaturization, flexibility, high cycling and retention stability, low programming energy and fast switching speed. Furthermore, systems with the added advantage of flexibility provide the opportunity to be integrated in next-generation devices, such as wireless sensors, roll-up displays and wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…High‐resolution scans of Pb 4f (as‐fabricated perovskite and SPTP) are shown in Figure 1e with the binding energies of Pb 4f located at 139.2 and 144.1 eV, indicating that Pb element in as‐fabricated perovskite and SPTP layer are 2+ oxidation state. [ 21,22 ] To further inspect the structure of the SPTP layer, X‐ray diffraction (XRD) patterns of the as‐fabricated perovskite (blue) and SPTP (red) films were obtained, as shown in Figure 1f, where the peaks indicated by green and yellow diamonds show the crystallization of CsPb 2 Br 5 and CsPbBr 3 , respectively. The XRD patterns showed that the as‐fabricated perovskite matched the crystal orientation of the typical CsPbBr 3 structure, whereas the SPTP film showed a crystal orientation corresponding to CsPbBr 3 and CsPb 2 Br 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the growth and annihilation modes of conductive filament depend on the mobility of electrochemically active metal cations, the redox reaction, and the nucleation of nanoscale metal filament. The migration of Ag + cations and the formation of dendrite-like Ag filament were experimentally demonstrated in the lateral Ag/PMMA@CsPbI 3 /Ag structure by SEM (Figure e–h) …”
mentioning
confidence: 88%
“…The migration of Ag + cations and the formation of dendrite-like Ag filament were experimentally demonstrated in the lateral Ag/PMMA@CsPbI 3 /Ag structure by SEM (Figure 3e−h). 42 In particular, Sun et al proposed the competitive mechanism between anion migration and cation migration and demonstrated that the resistive switching behaviors were highly dependent upon the film thickness in the Ag/MAPbI 3 /FTO structure. 45 In addition, the Ag electrode could react with halide ions to form AgX compounds, thus inducing more halogen vacancies in halide perovskite films and leading to the degradation of Ag electrode.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation